2021
DOI: 10.1093/cercor/bhab384
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Principles of White Matter Connectivity in the Human and Nonhuman Primate Brain

Abstract: Brains come in many shapes and sizes. Nature has endowed big-brained primate species like humans with a proportionally large cerebral cortex. Comparative studies have suggested, however, that the total volume allocated to white matter connectivity—the brain’s infrastructure for long-range interregional communication—does not keep pace with the cortex. We investigated the consequences of this allometric scaling on brain connectivity and network organization. We collated structural and diffusion magnetic resonan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 85 publications
3
20
0
Order By: Relevance
“…Surprisingly, we also did not recover notable influences of absolute brain size on hand preferences. An effect on lateralization strength was expected both on theoretical considerations ( Ringo et al, 1994 ) and empirical evidence from studies investigating intra- and interspecific covariation of brain size and overall cortical lateralization ( Kong et al, 2018 ; Ardesch et al, 2021 ). Why do anthropoid hand preferences not conform to these predictions?…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Surprisingly, we also did not recover notable influences of absolute brain size on hand preferences. An effect on lateralization strength was expected both on theoretical considerations ( Ringo et al, 1994 ) and empirical evidence from studies investigating intra- and interspecific covariation of brain size and overall cortical lateralization ( Kong et al, 2018 ; Ardesch et al, 2021 ). Why do anthropoid hand preferences not conform to these predictions?…”
Section: Discussionmentioning
confidence: 97%
“…By now, this idea has also been extended to non-human primates that habitually use tools ( Cashmore et al, 2008 ; Prieur et al, 2019 ). Moreover, neuroanatomical studies demonstrated that the expression of overall neural lateralization and hemispheric independence positively correlates with absolute brain size in primates ( Rilling and Insel, 1999 ; Karolis et al, 2019 ; Ardesch et al, 2021 ). Such a scaling relation was already hypothesized by Ringo et al, 1994 , and implies that the strength of individual handedness could also be tied to absolute brain size ( Hopkins, 2013a ; the concept does, however, not concern the direction of hand preferences).…”
Section: Introductionmentioning
confidence: 99%
“…For example, species with fewer commissural inter-hemispheric connections exhibit lower hemispheric mean-shortest-path (i.e., stronger intra-hemispheric connectivity), suggesting a similar connectivity conservation principle [3]. Likewise, using diffusion-weighted MRI data across 14 different primate species, another study reported negative allometric scaling of cortical surface area with white matter volume and corpus callosum cross-sectional area [2]. This scaling results in less space for white matter connectivity with increasing brain size, translating into larger brains with a relatively higher proportion of shortrange connections than long-range connections when compared with smaller brains [2].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, using diffusion-weighted MRI data across 14 different primate species, another study reported negative allometric scaling of cortical surface area with white matter volume and corpus callosum cross-sectional area [2]. This scaling results in less space for white matter connectivity with increasing brain size, translating into larger brains with a relatively higher proportion of shortrange connections than long-range connections when compared with smaller brains [2]. Collectively these studies highlight that the architecture of neural circuits and their physical embedding are intertwined, and the distribution of connections is such that it retains consistent global architectural features across phylogeny.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these considerations, it has been prominently proposed that foraging-related extractive tool use facilitated the evolution of hand preferences in humans to allow for more efficient object handling (Kimura, 1979;Frost, 1980), but this idea has also been extended to nonhuman primates that habitually use tools (Cashmore et al, 2008;Prieur et al, 2019). Moreover, neuroanatomical studies demonstrated that the expression of overall neural lateralization and hemispheric independence positively correlates with absolute brain size in primates (Rilling & Insel, 1999;Karolis et al, 2019;Ardesch et al, 2021). Such a scaling relation was already hypothesized by Ringo et al (1994) and implies that the strength of individual handedness could also be tied to absolute brain size (Hopkins, 2013b); the concept does, however, not concern the direction of hand preferences.…”
Section: Introductionmentioning
confidence: 99%